Penerapan Senam Tera sebagai Intervensi untuk Menurunkan Tekanan Darah pada Lansia Penderita Hipertensi di Desa Guwosari Wilayah Kerja Puskesmas Ngoresan - Winda Safitri; Didik Iman Margatot; Panggah Widodo (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Hypertension is one of the most common non-communicable diseases among older adults. If not managed properly, hypertension can increase the risk of various complications, including stroke, heart disease, and kidney failure. One of the non-pharmacological approaches that can be used to reduce blood pressure is Tera Gymnastics (Senam Tera). This study aimed to determine the effectiveness of Tera Gymnastics in reducing blood pressure among older adults with hypertension. This study employed a descriptive case study approach involving two older adults with hypertension in Guwosari Hamlet, RT 03 RW 27, Jebres, Surakarta. The intervention consisted of Tera Gymnastics sessions lasting 30–45 minutes, conducted three times a week. Blood pressure was measured before and after the intervention using a sphygmomanometer. After participating in the Tera Gymnastics intervention, both participants experienced a reduction in blood pressure. Mrs. S's blood pressure decreased from 160/94 mmHg to 139/80 mmHg, while Mrs. W's blood pressure decreased from 150/90 mmHg to 130/80 mmHg. Tera Gymnastics is an effective non-pharmacological intervention that can help reduce blood pressure in older adults with hypertension.